Internal residual stress originated from Bain strain and its effect on hardness in Fe–Ni martensite - Fukui, Daisuke; Nakada, Nobuo; Onaka, Susumu (Acta materialia, 2020)
To further understand the internal residual stress that is microscopically generated via martensitic transformation in steels, the origin of internal strain attributed to Bain correspondence between face-centered cubic (fcc) and body-centered cubic (bcc) was evaluated from macro- and micro-viewpoints and its effect on hardness was investigated in an interstitial free Fe-16%Ni martensite. Neutron diffractometry and electron backscatter diffraction analysis showed that body-centered cubic (bcc) crystal structure of as-quenched martensite contained elastic distortions leading to small tetragonality, even in martensitic steels without solute carbon, and that the extended [001]bcc of martensite tended to be parallel to fcc of prior fcc austenite. In addition, the combination of micro-scale focused ion beam (FIB) and high-precision digital image correlation techniques revealed that a micropillar fabricated by FIB processing within a martensite block was anisotropically deformed by the release of the residual strain distributed in as-quenched martensite in correspondence with the tetragonal distortions of the bcc crystal structure. These results prove that a small part of the Bain strain remained as an internal elastic residual strain and was microscopically distributed among Bain groups in lath martensite after martensitic transformation. Furthermore, the residual strain generated a hydrostatic internal stress, and therefore, the nanohardness decreased considerably by the micropillar fabrication accompanied by the release of the internal stress. This means that the internal residual stress in martensite among Bain groups influences the mechanical properties of martensitic steel. [Display omitted]